Artificial Intelligence: Transforming Industries, Enhancing Daily Life and Tackling Ethical Challenges - Patnaik, Raja (Journal of Educational Research and Policies, 2024)
Artificial Intelligence AI is rapidly becoming a vital component of modern life, transforming industries and enhancing everyday experiences. From healthcare to finance and education, AIs ability to automate processes, improve efficiency, and drive innovation is reshaping the world. With advancements in machine learning, natural language processing, and robotics, AI systems are increasingly capable of performing tasks that require human intelligence. However, as AI continues to evolve, it also presents ethical and societal challenges, such as job displacement, bias, and privacy concerns. This article explores the diverse applications of AI, its impact on various sectors, and the importance of responsible AI development to ensure a fair and inclusive future.